HRQoL and its association with clinical severity and service needs among individuals with a substance use disorder. - Stallvik, Marianne; Clausen, Thomas (Journal of Substance Use, 2017)
Health Related Quality of Life (HRQoL) has received more attention recently; however, there is still limited knowledge of the relationship between HRQoL in comorbid samples, and service needs within this population. The rate for additional psychological issues and the drop-out rate is known and reported high and investigating HRQoL might provide more answers on needs within this population. A multi-cite prospective study including 175 treatment seeking individuals from mid-Norway was studied at baseline and three months after treatment initiation. Data were gathered from a structured ASAM interview and a self-report survey covering the SF-36 items regarding HRQoL. The results showed significantly lower HRQoL scores among treatment seeking individuals with a substance use disorder, compared with scores from the general population. Higher psychological burden was associated with lower HRQoL at baseline. At follow-up HRQoL increased and significantly for Physical Function. In addition, the individuals with the lowest HRQoL scores on psychological items received more psychiatric program recommendation by ASAM. The high drop out among those who scored the lowest on HRQoL is of clinical importance. Both SF-36 and ASAM interview based software are considered to be valid and useful tools to retrieve patient centered and relevant information and should be used in a clinical setting to support individually tailored treatment.